Effect and mode of action of the Texel muscling QTL (TM-QTL) on carcass traits in purebred Texel lambs. (7th May 2014) - Macfarlane, J. M.; Lambe, N. R.; Matika, O.; Johnson, P. L.; Wolf, B. T.; Haresign, W.; Bishop, S. C.; Bünger, L.
<x content-type="archive" xml:space="preserve">Abstract</x> TM-QTL is a quantitative trait locus (QTL) on ovine chromosome 18 (OAR18) known to affect loin muscling in Texel sheep. Previous work suggested that its mode of inheritance is consistent with paternal polar overdominance, but this has yet to be formally demonstrated. This study used purebred Texel sheep segregating for TM-QTL to confirm its presence in the chromosomal region in which it was first reported and to determine its pattern of inheritance. To do so, this study used the first available data from a Texel flock, which included homozygote TM-QTL carriers (TM/TM; n=34) in addition to homozygote non-carriers (+/+; n=40 and, heterozygote TM-QTL-carriers inheriting TM-QTL from their sire (TM/+; n=53) or their dam (+/TM; n=17). Phenotypes included a wide range of loin muscling, carcass composition and tissue distribution traits. The presence of a QTL affecting ultrasound muscle depth on OAR18 was confirmed with a paternal QTL effect ranging from +0.54 to +2.82 mm UMD (s.e. 0.37 to 0.57 mm) across the sires segregating for TM-QTL. Loin muscle width, depth and area, loin muscle volume and dissected M. longissimus lumborum weight were significantly greater for TM/+ than +/+ lambs (+2.9% to +7.9%; P<0.05). There was significant evidence that the effect of TM-QTL on the various loin muscling traits measured was paternally polar overdominant (P<0.05). In contrast, there was an additive effect of TM-QTL on both live weight at 20 weeks and carcass weight; TM/TM animals were significantly (P<0.05) heavier than +/+ (+11.1% and +7.3%, respectively) and +/TM animals (+11.9% and +11.7%, respectively), with TM/+ intermediate. Weights of the leg, saddle and shoulder region (corrected for carcass weight) were similar in the genotypic groups. There was a tendency for lambs inheriting TM-QTL from their sire to be less fat with slightly more muscle than non-carriers. For example, carcass muscle weight measured by live animal CT-scanning was 2.8% higher in TM/TM than +/+ lambs (P<0.05), carcass muscle weight measured by carcass CT-scanning was 1.36% higher in TM/+ than +/+ lambs (P<0.05), and weight of fat trimmed from the carcass cuts was significantly lower for TM/+ than +/+ lambs (−11.2%; P<0.05). No negative effects of TM-QTL on carcass traits were found. Optimal commercial use of TM-QTL within the sheep industry would require some consideration, due to the apparently different mode of action of the two main effects of TM-QTL (on growth and muscling).